What Paul meant - Wills, Garry 1934- (Penguin Books, 2007)
All through history, Christians have debated Paul's influence on the church. Though revered, Paul has also been a stone on which many stumble. Unlike the Gospel writers, who carefully shaped their narratives many decades after Jesus' life, Paul wrote in the heat of the moment, managing controversy, and sometimes contradicting himself, but at the same time offering the best reflection of those early times. This interpretation of Paul's writing examines his tremendous influence on the first explosion of Christian belief and chronicles the controversy surrounding Paul through the centuries.--From publisher description.